Reverse Derivations on δ-prime rings (European Journal of Pure and Applied Mathematics, 2022)
In this paper, we generalized Posner’s theorem, then we extended Mayne’s theorem to get a main result, based on researches of many authors, presented by the theorem, if δ is a nonzero centralizing reverse derivations on a nonzero δ-ideal U of δ –prime ring R, then R is commutative.
Keywords: reverse derivation; prime ring; ideal